KNOWLEDGE AND ATTITUDES AMONG MEDICAL RESIDENTS TOWARDS THE RESPONDEAT SUPERIOR DOCTRINE - Andreas Onggo; Yoni Syukriani; Sani Tanzilah; Annisa Anwar Muthaher; Sigid Kirana Lintang Bhima; Tuntas Dhanardhono (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2026)
Background: Medical residents are doctors undergoing specialized training through an apprenticeship under attending physicians. The requirement for them to hold a special practice license raised questions about their extent of responsibilities in the event of a lawsuit when performing their duty.Objectives: This research investigates the knowledge and attitudes of medical residents towards the doctrine of respondeat superior, which pertains to liability in hierarchical medical contexts.Methods: Questionnaires were distributed to residents across seven universities in Indonesia, representing surgical, medical, and diagnostic specialist groups. Statistical analyses were performed using univariate, bivariate, and multivariate approaches.Results: Results showed that only 26.58% (n=538) of the participants understood the doctrine well, although they generally held a positive attitude towards it. There was no significant correlation between knowledge and attitudes or between specialist groups (all p>0.05). However, a significant correlation was found between residents’ levels and attitudes towards respondeat superior (p<0.01), indicating that higher-level residents exhibited more positive attitudes. Multidimensional scaling revealed surgical residents showing more significant divergence from those in medical programs.Conclusion: Results suggested although the attitude was positive, understanding regarding respondeat superior among residents is insufficient, particularly to clarify responsibilities among residents and supervisors. Therefore, specific education related to the matter is recommended.